Effect Of Chocolate and Exercise on Reducing Menstrual Pain (Dysmenorrhea) In Adolescent - Soerjo Hadijono (Chakra Brahmanda Lentera Institute, 2021)
Background: The problem of adolescent reproductive health is still a problem that needs attention. Many women experiences discomfort at the onset of menstruation, one of which is dysmenorrhea. Various attempts were made to relieve these symptoms is by acts of non-pharmacological such as exercise and giving chocolates. Purpose of this study was to determine the effect of the combination of chocolate and exercise to decrease menstrual pain (dysmenorrhea) in adolescents in SMPN 1 Bangkalan Methods: This method uses a method Quasi Experiment using a control time series design. The population in this study were students of SMP Negeri 1 Bangkalan who experienced dysmenorrhea. The sampling technique used in this study was simple random sampling with inclusion and exclusion criteria of 54 respondents who were divided into two groups with 27 respondents in each group. Results: The results showed that there was an effect of exercise and chocolate on decreasing menstrual pain with a sig value of 0.050 0.05 and an OR value of 5.263. In addition, there are also other factors that influence the decrease in menstrual pain, namely BMI with a sig value of 0.032 0.05 and an OR value of 0.214. Conclusion: there is an effect between the combination of exercise and chocolate in reducing menstrual pain (dysmenorrhea).